Specifically Regulated Pesticides in Florida -- Bromacil - Frederick M. Fishel (EDIS)
Certain individual pesticides or groups of pesticides have specific regulations that pertain to them. The Florida Department of Agriculture and Consumer Services (FDACS) is the agency responsible for determining these regulations under Chapter 5E-2, Florida Administrative Code – “Pesticides.” This guide will explain special regulations governing the use of bromacil in Florida.  This document is PI-75, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date October 2005.